Pneumocystis Jirovecii Pneumonia Diagnosis via Metagenomic Next-Generation Sequencing - Lu, Xiaoxiao; Zhang, Jianhui; Ma, Wentao; Xing, Lihua; Ning, Hanbing; Yao, Mengying (Frontiers in Medicine, 2022)
The incidence of non-HIV infected Pneumocystis Jirovecii Pneumonia (PJP) is increasing. The prognosis for non-HIV PJP is poor and diagnostic tests are of lower sensitivity in non-HIV patients. Metagenomic next-generation sequencing (mNGS) was compared with routine detection assays, including Gomori methenamine silver (GMS) stain and polymerase chain reaction (PCR) technique. Specimens of 4 bronchoalveolar lavages (BAL) and 1 lung tissue samples, were obtained from 4 non-HIV patients from our hospitals. Although both GMS and mNGS were positive for P. jirovecii with PCR as positive control, the testing time of mNGS was obviously shorter than GMS. What’s more, the results of mNGS were consistent with the traditional test results. Compared with the traditional GMS method, mNGS has absolute advantages. However, the issue with PJP presentations having atypical symptoms and ambiguous imaging features persists, and the disease can easily be ignored. Secondly, PJP progresses rapidly in non-HIV infected patients and can cause severe respiratory failure with unfavorable prognosis. This study affirms that mNGS can be used to quickly and accurately diagnose PJP, but a combination of clinical judgement of symptoms, laboratory testing, and imaging examination is required to make a comprehensive judgment along with mNGS test results.